The Objective Effect of Breast Implant Removal and Capsulectomy on Pulmonary Function. Issue 6 (June 2021) - Wee, Corinne E.; Younis, Joseph; Boas, Samuel; Isbester, Kelsey; Smith, Arvin; Harvey, Donald J.; Patil, Nirav; Kumar, Anand R.; Feng, Lu-Jean
Abstract : Background: Breast Implant Illness after aesthetic breast augmentation remains a poorly-defined syndrome. Prior published studies have identified difficulty breathing as a symptom, but definitive improvement in breathing following breast implant removal remains understudied. We hypothesized that patients presenting with breathing symptoms attributed to breast implants would have objective improvement in pulmonary function tests after complete implant/capsule explantation. Methods: A retrospective study of all patients who underwent investigation for symptomatic breast implants by a single surgeon over 2 years was conducted. Paired T-tests were used to compare PFTs before and after surgery. Multivariate analyses and linear regression models were used to examine the impact of patient- and implant-related factors, including size and texture on PFT changes. Results: Sixty-nine patients met inclusion criteria. Forced vital capacity (mean pre: 3.67 ± 0.61 L versus post: 3.82 ± 0.55 L), forced expiratory volume (2.78 ± 0.44 L versus 2.89 ± 0.39 L), and peak expiratory flow rate (5.91 ± 1.43 L versus 6.56 ± 0.96 L) were significantly improved postoperatively ( P = 0.004, 0.01, 0.0001, respectively). Textured implants were associated with a greater improvement in PFTs after their removal ( P = 0.009). Implant size and capsular contracture, even when controlled relative to body mass index, were not independent predictors of improvement. Conclusions: This study demonstrates that patients presenting with symptomatic breast implants with pulmonary complaints had significant improvement in pulmonary function after complete implant/capsule explantation. Forced vital capacity, forced expiratory volume, and peak expiratory flow rate consistent with a restrictive pattern of ventilation reliably improved in this symptomatic cohort. Textured implants were a significant predictive variable for improvement in pulmonary function.